FGF2 activates TRPC and Ca2+ signaling leading to satellite cell activation - Liu, Yewei (Frontiers in Physiology, 2014)
Satellite cells, as stem cells of adult skeletal muscle, are tightly associated with the differentiated muscle fibers and remain quiescent in the absence of muscle damage. In response to an injury, the quiescent satellite cell is activated by soluble factors, including FGFs released from injured myofibers. Using immunostaining, we here first show that TRPC1 channels are highly expressed in satellite cells attached to muscle fibers. Since CD34, a traditional stem cell marker, was recently found to be expressed in skeletal muscle satellite cells we labeled living satellite cells in their physiological niche associated with host FDB fibers using anti-CD34-FITC antibody. We then monitored intra-cellular calcium in anti-CD34-FITC labeled satellite cells attached to muscle fibers using the calcium sensitive dye X rhod-1 which has little fluorescence cross talk with FITC. FGF2 increased intracellular calcium in satellite cells, which was antagonized by the TRPC channel blocker SKF 96365. Immunostaining showed that NFATc3 is highly expressed in satellite cells, but not in host FDB fibers. Elevation of intracellular calcium by FGF2 is accompanied by nuclear translocation of NFATc3 and NFATc2 and by an increase in the number of MyoD positive cells per muscle fiber, both of which were attenuated by TRPC blocker SKF 96365. Our results suggest a novel pathway of satellite cell activation where FGF2 enhances calcium influx through TRPC, and the increased cytosolic calcium leads to both NFATc3 and NFATc2 nuclear translocation and enhanced number of MyoD positive satellite cells per muscle fiber.